2018
DOI: 10.1186/s13046-018-0807-2
|View full text |Cite
|
Sign up to set email alerts
|

Downregulated miR-98-5p promotes PDAC proliferation and metastasis by reversely regulating MAP4K4

Abstract: BackgroundThe aberrant expression of microRNAs (miRNAs) has emerged as important hallmarks of cancer. However, the molecular mechanisms underlying the differences of miRNA expression remain unclear. Many studies have reported that miR-98-5p plays vital functions in the development and progression of multiple cancers. However, its role in pancreatic ductal adenocarcinoma (PDAC) remains unknown.MethodsThe expression of miR-98-5p and its specific target gene were determined in human PDAC specimens and cell lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 42 publications
2
44
0
Order By: Relevance
“…25 In addition, miR-98-5p can promote the development of pancreatic ductal adenocarcinoma by downregulating mitogen-activated protein 4 kinase 4 (MAP4K4) and inhibiting the downstream mitogen-activated protein kinase/extracellular regulated protein kinases (MAPK/ ERK) signaling pathway. 26 However, hsa-let-7a-5p, hsa-let -7b-5p and hsa-let-7c-5p play an important role in the occurrence and development of colorectal cancer, multiple myeloma and acute lymphoblastic leukemia. [27][28][29] This finding provides a theoretical basis for understanding the working mechanism of hsa_circRNA_012515 in the occurrence and development of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…25 In addition, miR-98-5p can promote the development of pancreatic ductal adenocarcinoma by downregulating mitogen-activated protein 4 kinase 4 (MAP4K4) and inhibiting the downstream mitogen-activated protein kinase/extracellular regulated protein kinases (MAPK/ ERK) signaling pathway. 26 However, hsa-let-7a-5p, hsa-let -7b-5p and hsa-let-7c-5p play an important role in the occurrence and development of colorectal cancer, multiple myeloma and acute lymphoblastic leukemia. [27][28][29] This finding provides a theoretical basis for understanding the working mechanism of hsa_circRNA_012515 in the occurrence and development of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Through analyzing the miRNA and mRNA expression connection in BC patients, we identi ed a novel hsa-miR-98-5p/IGF1 axis that may play a crucial role in BC. hsa-miR-98-5p has a controversial role in human cancers as it can function as either tumor suppressor or oncogene [22,23]. For example, Fu and co-workers showed that downregulation of hsa-miR-98-5p could promote the development of pancreatic ductal adenocarcinoma via inversely regulating the expression of MAP4K4, indicating the tumor suppressive role of hsa-miR-98-5p [22].…”
Section: Discussionmentioning
confidence: 99%
“…hsa-miR-98-5p has a controversial role in human cancers as it can function as either tumor suppressor or oncogene [22,23]. For example, Fu and co-workers showed that downregulation of hsa-miR-98-5p could promote the development of pancreatic ductal adenocarcinoma via inversely regulating the expression of MAP4K4, indicating the tumor suppressive role of hsa-miR-98-5p [22]. On the contrary, Wang et al showed hsa-miR-98-5p was enriched expression in epithelial ovarian cancer, and regulated the sensitive of cancer cells to cisplatin [23].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, multiple miRNAs have also been found abnormally expressed in tumors and regulate their cell biological processes ( 13 ). MiR-98-5p is one member of miRNAs, and its downregulation has been shown to promote pancreatic ductal adenocarcinoma (PDAC) proliferation and metastasis ( 14 ). In addition, it is found that miR-98-5p enhances the sensitivity of epithelial OC to cisplatin ( 15 ).…”
Section: Introductionmentioning
confidence: 99%